Microvascular integrity plays an important role for graft survival after experimental skin transplantation - Motsch, Benjamin; Heim, Christian; Koch, Nina; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, Stephan M. (Transplant Immunology, 2015)
Every transplanted organ relies on a reliable and sound vascular system. Therefore, our study focused on the investigation if platelet inhibition alone or combined with mTOR-inhibition has a beneficial effect on the microvascular integrity in allogeneic murine skin grafts.Skin transplantation was performed from fully MHC-mismatched C57BL/6 (H-2b) donors to CBA/J (H-2k) recipient mice. Skin allograft recipients were assigned to several experimental groups and either treated with clopidogrel alone, everolimus alone or a combination of both. Graft survival was evaluated and transplants were harvested after 8 days and analyzed for CD31 and C4d by immunohistochemistry.Untreated allografts showed a reduced amount of CD31 on postoperative day 8 as well as an increase in C4d compared to isografts. All treated animals showed a significant improvement regarding CD31 [1577.7 ± 200.4 (clopidogrel)/1702.8 ± 151.1 (clopidogrel + everolimus) vs. 479.7 ± 184.2 (control), n = 8, p b 0.05] and C4d [420.9 ± 70.9 (clopidogrel)/324.5 ± 77.3 (clopidogrel + everolimus) vs. 772.4 ± 159.7 (control), n = 8, p b 0.05]. In addition, skin grafts of animals treated with clopidogrel and everolimus survived significantly longer compared to untreated controls [19.2 ± 4.2 d vs. 12.8 ± 2.4 d, n= 10, p b 0.05].In this study we could show that clopidogrel alone and in combination with everolimus substantially improved microvascular integrity and resulted in increased survival time of skin grafts.
EVALuna2:16101